Young adults’ considerations for whole genome sequencing - Barnard, Pepita M. (2021)
Background: Young adults’ (YAs) attitudes regarding undertaking, receiving and sharing genomic information will inform translation of genomic technologies into improvements in health and healthcare. They have greater exposure than those before them with increasing opportunities to access whole genome sequencing (WGS). As YAs, the potential benefits from WGS, through preventative and therapeutic measures lie ahead. WGS results may offer relevant new information to them and their relatives. By nature of genomic data, the act of sharing WGS results with genomic databases or databanks has the potential to improve societal health. Yet, as a group, their preferences towards undertaking WGS and related individual characteristics are little known, requiring further examination. Theoretical models to support research about attitudes and behaviour have not been appraised to address their suitability for use in the context of WGS. Several established models for technology acceptance and health-related behaviours exist yet their appropriateness to the context of WGS remains untested. Appraisal and considered use of theoretical models for research design and analytical purposes is important to increase rigour of empirical studies. Each model reflects different characteristics, influencing the lines of research enquiry. Advancement of appropriately underpinned research facilitates development of comparable empirical research in particular fields of study, such as genomics. Continued examination of the fit between the phenomenon being explored and the theoretical underpinnings themselves is also necessary. This allows gaps to be recognised between models used and reality, furthering understanding and model development or refinement. This PhD thesis was in partnership with Nottingham University Hospitals NHS Trust. Methods: Studies with YAs were informed by literature that related to their use of WGS and theoretical models that could reflect undertaking WGS. A quantitative survey study was undertaken with 112 YAs to identify relationships between their sharing preferences and their gender, educational attainment, STEMM background and genetic knowledge. A WGS Pathway was proposed to reflect the steps of undertaking WGS, receiving results and sharing them. The Proposed WGS Pathway was used to structure the question order for a semi-structured interview study with 11 YAs. Qualitative data were collected and analysed using theme based content analysis. This method simulated YAs’ references and reasons, captured in the order they might occur if the YAs imagined undertaking WGS. An appraisal of theoretical models was undertaken using data collected in the YAs’ studies to inform their relevance and fit to WGS. A WGS framework, constructed to represent YAs’ consideration factors along the WGS Pathway was evaluated by domain experts, who ranked the WGS framework’s factors by likelihood and importance, and shared their views about the Proposed WGS Pathway. Results: Characteristics such as gender and genetic knowledge were statistically significant in relation to YAs’ willingness to engage with and share information about WGS. Themes from interviews indicated YAs had interests related to health and self-discovery. Health professionals and trusted researchers were seen positively for sharing WGS results information with. Appraisal of theoretical models indicated the Theory of Planned Behaviour (TPB) was best placed to support a WGS framework representing findings from the YA studies. From TPB factors presented to them, the domain experts decided utility-related attitudes and perceived behavioural control (PBC) were more important than subjective norms (SN) and external factors. They also identified differences between what factors they perceived YAs would consider compared to those they thought were actually important. Conclusion: The findings demonstrated the significant impact individual characteristics had on YAs’ attitudes towards undertaking WGS, receiving results and sharing genetic information. Analysis of YAs’ responses illustrated areas for further investigation including expectations of WGS and sharing preferences. Appraisal of theoretical models identified the need for a wide lens to incorporate findings about undertaking WGS. Domain experts pointed to a need for YAs to undertake some form of pre-WGS intervention so they may take a step back to make an informed decision about the undertaking. Implications for Practice: The WGS framework offers a successful translation of WGS into services to improve health outcomes for YAs. A clearer understanding of knowledge and educational needs when choosing to undertake WGS, receive results, and make sharing decisions would better inform individuals. Further exploration of YAs’ sharing preferences and attitudes regarding health professionals would contribute to a better understand of factors affecting communication related to WGS and the resulting information. As genomics permeate more into the realms of the quantified self for self-care and healthcare, views of people who are undertaking, receiving and managing their WGS information needs further exploration so systems and services may be designed to meet their evolving needs.